The formulation of financial, governance and social index of Malaysian Islamic Banks: An integrative approach - Marsidi, A.; Annuar, H.A; Abdul Rahman, A.R (Elsevier B.V., 2016)
The study proposes and discusses the development of an index of Islamic Financial and Social Reporting (IFSR) for Islamic banks. The index of IFSR is carefully developed based on the relevant and applicable standards, guidelines and literature from an Islamic perspective such as the Malaysian Accounting Standards Board (MASB), Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI), Islamic Financial Services Board (IFSB), Bank Negara Malaysia (BNM) and Islamic social reporting literature. The index is developed in three parts, namely, financial, social, and auditing and governance. The items within the finance section are developed to ensure that the Islamic banks disclose relevant financial information. The items for the social part aim to ensure that the Islamic banks provide the relevant information regarding social and environment. The items within the auditing and governance part are developed to ensure that the Islamic banks provide relevant information regarding the monitoring and supervising activities that the Islamic banks have undertaken. The IFSR index may be lacking in terms of its usage generalisability as it is specifically developed for IFIs. The developed index of IFSR aims to promote a more appropriate level of disclosure among the Islamic banks. The need for the index is motivated by the growing importance of Islamic banks, not only from the economic perspective but also from the social perspective